From nickel-metal hydride batteries to advanced engines: A comprehensive review of hydrogen's role in the future energy landscape - Nivedhitha, K. S.; Banapurmath, N. R.; Yaliwal, V. S.; Umarfarooq, M. A.; Sajjan, Ashok M.; Venkatesh, R.; Hosmath, R. S.; Beena, T.; Khan, T. M. Yunus; Kalam, M. A.; Soudagar, Manzoore Elahi M.; Agbulut, Umit (PERGAMON-ELSEVIER SCIENCE LTD, 2024)
Hydrogen has emerged as a disruptive force in the energy landscape, poised to revolutionise the automotive sector with its use in both fuel cell and internal combustion engines. This article covered two topics: application of metal hydrides for hydrogen storage and use of cutting-edge engine technology in hydrogen-powered vehicles. This article begins with discussing the different characteristics of materials that are used to store hydrogen. Metal hydrides, rare earth elements, and carbon-based compounds are among the materials that are carefully studied in this work. Understanding how effectively these materials can store hydrogen was another goal of this research. In order to fully utilize hydrogen's potential, it is imperative to compare them with conventional fossil fuels highlighting their significance. Additionally, this study explains how hydrogen can be used to power existing and newer automobile vehicles. Also discussed are the viability and potential mechanisms of operation for various hydrogen-using engine technologies, such as compression ignition and spark ignition engines. Cutting-edge on vehicles with fuel cell and engine technology powered by hydrogen along with their challenges are explained. They include discussions of several techniques such as homogenous charge compression ignition (HCCI), dualfuel, and reactivity-controlled combustion ignition (RCCI). Additionally, the advantages and disadvantages of utilizing hydrogen in these state-of-the-art engine technologies are discussed. This research offers insights on the future of automobiles in addition to hydrogen storage. This study points the path towards a more creative and sustainable energy environment in which hydrogen plays a major role in the storage and utilization for automobile vehicles.
Keywords: Hydrogen absorption; Desorption; Mechanical alloying; Activation energy; Hydrogen utilization; Direct injection; COMPRESSION IGNITION ENGINE; DUAL-FUEL ENGINE; EXHAUST-GAS RECIRCULATION; DUTY DIESEL-ENGINE; COMBUSTION CHARACTERISTICS; EMISSION CHARACTERISTICS; STORAGE PERFORMANCE; PRODUCER GAS; HCCI ENGINE; ELECTROCHEMICAL PROPERTIES; Chemistry; Electrochemistry; Energy & Fuels